A Randomized, Placebo-Controlled Study of High-Dose Baclofen in Alcohol-Dependent Patients—The ALPADIR Study. (19th May 2017) - Reynaud, Michel; Aubin, Henri-Jean; Trinquet, Francoise; Zakine, Benjamin; Dano, Corinne; Dematteis, Maurice; Trojak, Benoit; Paille, Francois; Detilleux, Michel
Abstract: Aims: Alcohol dependence is a major public health issue with a need for new pharmacological treatments. The ALPADIR study assessed the efficacy and safety of baclofen at the target dose of 180 mg/day for the maintenance of abstinence and the reduction in alcohol consumption in alcohol-dependent patients. Methods: Three hundred and twenty adult patients (158 baclofen and 162 placebo) were randomized after alcohol detoxification. After a 7-week titration, the maintenance dose was provided for 17 weeks, then progressively decreased over 2 weeks before stopping. Results: The percentage of abstinent patients during 20 consecutive weeks (primary endpoint) was low (baclofen: 11.9%; placebo: 10.5%) and not significantly different between groups (OR 1.20; 95%CI: 0.58 to 2.50; P = 0.618). A reduction in alcohol consumption was observed from month 1 in both groups, but the difference of 10.9 g/day at month 6 between groups, in favour of baclofen, was not statistically significant ( P = 0.095). In a subgroup of patients with high drinking risk level at baseline, the reduction was greater with a difference at month 6 of 15.6 g/day between groups in favour of baclofen ( P = 0.089). The craving assessed with Obsessive-Compulsive Drinking Scale significantly decreased in the baclofen group ( P = 0.017). No major safety concern was observed. Conclusions: This study did not demonstrate the superiority of baclofen in the maintenance of abstinence at the target dose of 180 mg/day. A tendency towards a reduction in alcohol consumption and a significantly decreased craving were observed in favour of baclofen. Short summary: Baclofen was assessed versus placebo for maintenance of abstinence and reduction in alcohol consumption in alcohol-dependent patients. This study did not demonstrate the superiority of baclofen in the maintenance of abstinence. A tendency towards a reduction in alcohol consumption and a significantly decreased craving were observed in favour of baclofen.